Co-distribution of cysteine cathepsins and matrix metalloproteases in human dentin. (February 2017) - Scaffa, Polliana Mendes Candia; Breschi, Lorenzo; Mazzoni, Annalisa; Vidal, Cristina de Mattos Pimenta; Curci, Rosa; Apolonio, Fabianni; Gobbi, Pietro; Pashley, David; Tjäderhane, Leo; Tersariol, Ivarne Luis dos Santos; Nascimento, Fábio Dupart; Carrilho, Marcela Rocha
Highlights: CT-B and CT-K co-occur on the dentin organic matrix, but they are differently distributed. Both MMPs and CTs are responsible for dentin proteolytic activity. The activity of MMPs is preponderant over CTs in sound dentin matrix. Abstract: It has been hypothesized that cysteine cathepsins (CTs) along with matrix metalloproteases (MMPs) may work in conjunction in the proteolysis of mature dentin matrix. The aim of this study was to verify simultaneously the distribution and presence of cathepsins B (CT-B) and K (CT-K) in partially demineralized dentin; and further to evaluate the activity of CTs and MMPs in the same tissue. The distribution of CT-B and CT-K in sound human dentin was assessed by immunohistochemistry. A double-immunolabeling technique was used to identify, at once, the occurrence of those enzymes in dentin. Activities of CTs and MMPs in dentin extracts were evaluated spectrofluorometrically. In addition, in situ gelatinolytic activity of dentin was assayed by zymography. The results revealed the distribution of CT-B and CT-K along the dentin organic matrix and also indicated co-occurrence of MMPs and CTs in that tissue. The enzyme kinetics studies showed proteolytic activity in dentin extracts for both classes of proteases. Furthermore, it was observed that, at least for sound human dentin matrices, the activity of MMPs seems to be predominant over the CTs one.